Workshop Report on Biodiversity and Pandemics of the Intergovernmental Platform on Biodiversity and Ecosystem Services. Daszak, P., Amuasi, J., das Neves, C. G., Hayman, D., Kuiken, T., Roche, B., Zambrana-Torrelio, C., Buss, P., Dundarova, H., Feferholtz, Y., Földvári, G., Igbinosa, E., Junglen, S., Liu, Q., Suzan, G., Uhart, M., Wannous, C., Woolaston, K., Mosig Reidl, P., O’Brien, K., Pascual, U., Stoett, P., Li, H., Ngo, H. - IPBES (Zenodo, 2020)
The IPBES Bureau and Multidisciplinary Expert Panel (MEP) authorized a workshop on biodiversity and pandemics that was held virtually on 27-31 July 2020 in accordance with the provisions on “Platform workshops” in support of Plenary-approved activities, set out in section 6.1 of the procedures for the preparation of Platform deliverables (IPBES-3/3, annexe I). This workshop report and any recommendations or conclusions contained therein have not been reviewed, endorsed or approved by the IPBES Plenary. The workshop report is considered supporting material available to authors in the preparation of ongoing or future IPBES assessments. While undergoing a scientific peer-review, this material has not been subjected to formal IPBES review processes. Workshop report: “IPBES Pandemics Workshop Report 20201029 v1.1.pdf” This workshop report is released in a non-laid out format. It will undergo minor editing before being released in a laid-out format. Executive summary: “IPBES Pandemics Workshop Executive Summary 20201028 v1.0.pdf” To get the latest version of the report visit https://doi.org/10.5281/zenodo.4147317 For inquiries, please contact secretariat@ipbes.net https://ipbes.net/events/ipbes-workshop-biodiversity-and-pandemics
Version Number: 1.3
Keywords: Biodiversity; COVID-19; IPBES; Pandemics